Competitors or Complements: A Meta-analysis of the Effect of Airbnb on Hotel Performance. (September 2022) - Yang, Yang; Nieto García, Marta; Viglia, Giampaolo; Nicolau, Juan Luis
The rise of peer-to-peer accommodation has challenged the traditional hotel business model. A lingering question is the effect of Airbnb supply on hotel performance. By analyzing 466 estimates from 33 different studies, our results reveal that the negative effect of Airbnb supply on hotel performance is moderate. The meta-regression of effect size recognizes the significant effects of different factors on the strength of the negative effect. In particular, the negative effect is smaller for high-end (vs. low-end) hotels, and its magnitude is shrinking over time. Additionally, the detrimental effect is less pronounced for European (vs. Asian) hotels. The study also reports that negative effects are more common in research published in academic journals. The synthesis of the effects across existing studies contributes to a robust and comprehensive understanding of the impact of Airbnb supply on hotel performance.